(untitled) (GUB Journal of Science and Engineering, 2024)
The comprehensive idea of lean manufacturing emphasizes the identification and removal of wastes related to production. Increased productivity, shorter lead times, improved line balancing, lower work in progress (WIP), higher quality, more adaptable designs, lower costs, etc. are all major objectives of applying lean tools. This study aims to investigate how lean manufacturing techniques might enhance manufacturing efficiency in Bangladeshi RMG sector. The sewing section of a small scale garment industry was the focus of this study. In the study, the existing line layout of a trouser style was examined using value stream mapping which contributed to the identification of numerous waste in the existing layout. In order to change the current status of the sewing section, the workplace was organized by 5S tools to remove wastes identified by VSM followed by altering the conventional longer line layout into three cell of work station as suggested by cellular manufacturing. After implementation of these lean tools, results observed include, production output is increased by 17.80%, efficiency is increased by 12.46%, SMV of product is standardized to 18.68 min., defects per hundred units is reduced to 10% and order change over time is reduced by 37%. The conclusions reached during the execution of this implementation study are realistic and applicable in industries with similar structures. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 10(1), 2023 P 27-36